Julia Waters. The Mauritian Novel: Fictions of Belonging. Liverpool UP, 2018. - Patrick H Moneyang (Studies in 20th & 21st Century Literature, 2020)
Review of Julia Waters. The Mauritian Novel: Fictions of Belonging. Liverpool UP, 2018. x + 236 pp.
Keywords: Belonging; Mauritian Fictions